A dictionary of marketing / Charles Doyle - Doyle, Charles
This is an accessible A-Z guide to all areas of marketing. Covering traditional techniques and theories as well as the latest terms and concepts in e-marketing and search engine optimization, this is the ideal reference for students and practitioners of marketing.